Problems of psychological support of professional activity of the employees of the State Penitentiary Service of Ukraine (Law and Safety, 2018)
It has been noted that official activities of the employees of the State Penitentiary Service (SPS) of Ukraine is directly related to the presence of a significant number of stressful factors and requires the comprehensive use of psychological tools and technologies. This affects the efficiency of professional activities of the specialists within penitentiary sphere. Taking into account the special conditions of professional activity of the employees of the SPS of Ukraine, the author has distinguished the main directions of the system of psychological support of professional activity of the employees of the SPS of Ukraine.The author has analyzed the following directions of the system of psychological support of professional activity of the employees of the State Penitentiary Service of Ukraine: professional psychological selection, psychological support of professional activity, professional psychological training of personnel and provision of recommendations to the management board. The author has distinguished the following tasks of the professional psychological selection of the employees for the SPS of Ukraine: assistance to citizens in choosing a particular specialty through professional counseling on the basis of studying individual and psychological characteristics and professional interests of future employees; determining the degree of conformity (inconsistency) of psychological data of a candidate or training the requirements of a specialty; the development of propositions for the rational allocation of employees to primary positions, etc. It has been noted that psychological support of the service of the personnel of the SPS of Ukraine envisages: monitoring of the socio-psychological climate within the staff and its maintenance at the proper level; psychodiagnostics of the personnel; correction of a personality, taking into account the results obtained during psychodiagnostics; provision of recommendations for the management board on deployment of personnel taking into account the results of psychodiagnostics; primary psychological prevention among penitentiary staff, etc. The professional psychological training of the employees of the SPS of Ukraine is considered as a purposeful process for the formation and development of personal qualities and traits of specialists that would meet the requirements of their professional activities.
Keywords: psychological provision; psychological support; special conditions of activity; penitentiary activity; State Penitentiary Service of Ukraine